The best country in the world: The surprising social mobility of New York's Irish famine immigrants - Tyler Anbinder; Cormac Ó Gráda; Simone Wegge (University College Dublin, UCD School of Economics, 2021)
We use databases we have created from the records of New York's Emigrant Savings Bank, founded by pre-Famine Irish immigrants and their children to serve Famine era immigrants, to study the social mobility of bank customers and, by extension, Irish immigrants more generally. We infer that New York's Famine Irish had a greater range of employment opportunities open to them than perhaps commonly acknowledged, and that the majority were eventually able to move a rung or two up the American socioeconomic ladder, supporting the conviction of many Famine immigrants that the U.S. was indeed "the best country in the world.
Keywords: N0; N3; J6; G21; 330; famine; migration; Ireland; New York